(untitled) (Scientific journal of the Fergana State University, 2023)
The article compares classical Persian vowels with modern Tajik vowels. Due to the fact that the classical Persian language is divided into two groups, some words are written and read in different ways today. In particular, the modern Tajik language is very different from the classical Persian language due to the fact that it has moved away from the southern dialects of the Persian language due to various geopolitical reasons and has changed the alphabet several times, as well as it has developed in a separate environment under the influence of other languages. These changes are visible on phonological, morphological, and syntactic and stylistic levels. During the detection of these changes, it shows the direction in which the language is moving and the reasons.